USING A TONGUEFISH CYNOGLOSSUS AREL BLOCH & SCHNEIDER, 1801 AS BIOINDICATOR OF METAL CONTAMINATION IN HALONG - CAT HAI AREA - Dung, Le Quang (Vietnam Journal of Marine Science and Technology, 2014)
In order to observe metal contamination and to evaluate the risk for human consumption in Ha Long - Cat Hai area, the level of ten trace metals (As, Cd, Co, Cr, Mn, Cu, Zn, Pb and V) was determined in muscle and liver of the tonguefish Cynoglossus arel collected in March, 2012 from Cat Hai - Ha Long coastal waters. The results indicated that the level of almost of all metals detected in muscle was lower than those in liver of C. arel, excepted for As. Characteristically, the level of Cd and Pb in liver was much higher than that in muscle, this might relate to detoxification function of liver. On the other hand, the metal levels in both toungefish’s muscle and liver specimens collected from Ha Long were higher than those from Cat Hai, especially Cd and Pb. This result indicated that this area showed the higher risk of metal pollution than Cat Hai. Furthermore, there was negative or no correlation between the level of these metals in toungefish’s muscle and its body weight. Some possible reasons for this correlation was documented on this paper. At the studied duration, the metal levels in fish’s muscle did not represent a risk for human consumption according to safety limits set by Ministry of Health. However, the high level of total asenic in fish at the all study sites suggested further study on the asenic speciations should be conducted in order to assess acurately the potential ecological risk and consumption protection.